Deltamethrin impact in a cabbage planted soil: Degradation and effect on microbial community structure. (April 2019) - Bragança, Idalina; Mucha, Ana P.; Tomasino, Maria P.; Santos, Filipa; Lemos, Paulo C.; Delerue-Matos, Cristina; Domingues, Valentina F.
Abstract: Synthetic pyrethroids (SPs) are one of the most common pesticides used worldwide. Their use has greatly increased in the last decades and its' continuous application lead to added pesticides concentration in soil. Consequently, SPs may enter the food chain, affecting the environment and human health. The degradation over time of the pyrethroid pesticide deltamethrin applied to cabbages was monitored. The evolution was followed both on cabbages and the surrounding soils, and the soil microbial community characterized by next-generation sequencing of the 16S rRNA gene. The main shift in the microbial community structure was observed during the first 30 days after pesticides' application. The modification in the microbial community composition, where an increased abundance of Nocardioides sp. and Sphingomonas sp. were observed, was correlated respectively with the conversions of deltamethrin and its metabolite, 3-phenoxybenzoic acid (3-PBA). Although deltamethrin was not found in any of the tested samples (soil and cabbage) after 180 days, it caused an environmental impact much further than the 7 days security interval. These findings suggest that deltamethrin application can disturb soil microbial community and that natural biodegradation can have an important part in pesticides soil decontamination. Graphical abstract: Image 1 Highlights: Monitoring of deltamethrin on the applied cabbage and soils over time. NGS as a tool to understand how microbial communities responded to deltamethrin application. Natural microbial community potentially biodegrades deltamethrin and 3-PBA. Shifts in soil microbial community structure after 30 days of pesticide application.